Nursing students’ perceptions of peer learning as a learning model in clinical practice and students’ learning through peer learning - an evaluation study - Karen Johanne Ugland Vae; Karen Johanne Vae; Helga Karin Kvalevaag; Anna Löfmark (Nordisk Tidsskrift for Helseforskning, 2017)
The study is an evaluation of peer learning, a model for learning in clinical practice where two students learn together and are supervised by one preceptor. The aim was to gain knowledge about how the nursing students experienced peer learning as a learning model when it was introduced in a hospital ward. The study was performed using a questionnaire with open and closed questions from 23 students.The results show that students experienced good control over the tasks they were responsible for and perceived increased independence and responsibility for the patients they cared for depending on the organization and clear structure in the model. Peer learning provided a good and instructive collaboration where students discussed and supported each other. Some students wanted a longer period with one preceptor before starting peer learning, and some students mentioned it could be challenging to be supervised by two preceptors in the peer learning period. However, the majority suggested peer learning as a permanent teaching model in clinical practice.